2022
DOI: 10.3389/fvets.2022.998192
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning from crates to free farrowing: A roadmap to navigate key decisions

Abstract: There are animal welfare concerns about the continued use of permanent crating systems for farrowing and lactating sows, which is the most prevalent maternity system in global pig production. Greater societal attention in recent years has culminated in changes (or proposed changes) to regulations as well as market-driven initiatives to move away from crated systems. Transitioning from farrowing crates to systems that allow the sow greater freedom of movement and behavioral expression requires a number of key d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…Moreover, it should be said that the piglets’ mortality recorded in this study during lactation in both the experimental groups is higher than those reported in the literature for hyperprolific sows (Baxter et al [ 40 ] reported a lactational mortality close to 15%), but it might be related to the temporary crating of the sows in the farrowing pen. In fact, free lactation is reported as one of the major causes of piglets’ mortality due to crushing [ 41 , 42 ]. In the present study, lactation efficiency was improved in the group of treated sows.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it should be said that the piglets’ mortality recorded in this study during lactation in both the experimental groups is higher than those reported in the literature for hyperprolific sows (Baxter et al [ 40 ] reported a lactational mortality close to 15%), but it might be related to the temporary crating of the sows in the farrowing pen. In fact, free lactation is reported as one of the major causes of piglets’ mortality due to crushing [ 41 , 42 ]. In the present study, lactation efficiency was improved in the group of treated sows.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence in the livestock industries that improved human-animal interactions may enhance job-related characteristics, such as job satisfaction, motivation and commitment, thereby potentially improving the stockperson's job performance (Hemsworth and Coleman, 2011;Hemsworth et al, 2018). Therefore, if the stockperson's attitude towards interacting with farrowing and lactating sows is negative as a consequence of sow handling difficulties, personal safety issues and inexperience (Marchant Forde, 2002;Baxter and Edwards, 2022), the stockperson's job satisfaction and commitment is likely to deteriorate with adverse consequences on work motivation and commitment and consequently work performance.…”
Section: Housing and Human-animal Interactionsmentioning
confidence: 99%
“…This information was used to update the recommended space requirements of sows during farrowing and lactation . A more recent review by Baxter et al (2022) emphasised the importance of the quality of space also, in terms of pen design and functionality and enabling the expression of fundamental behaviours including locomotion, nest building, and sow-piglet interactions. considered that while temporary confinement systems are the least costly, least risky 'alternative' to farrowing crates, they offer less in the way of improving sow welfare compared to loose farrowing and lactation housing systems.…”
Section: Piglet Mortalitymentioning
confidence: 99%
“…The weaker a piglet, the less capable it is to react to posture changes of the sow and to avoid being crushed or trampled (8, 10-16). To protect piglets from the risk of being crushed, farrowing crates are used almost everywhere in the world (17)(18)(19). Multiple studies showed that pre-weaning mortality is higher in non-crated than in crated housing systems of the farrowing and lactating sow (reviewed by 17,18,20).…”
Section: Introductionmentioning
confidence: 99%